Identifikasi Morfologi Reproduksi Dan Perkembangan Bryophyta Pada Lumut Daun (Octoblepharum albidum) di Kawasan Kampus Satu UIN Sunan Gunung Djati Bandung - Siti Riyani; Sofi Intan Nurhidayah; Sri Muna Rahayu Putri Pratama; Virna Fianarita Rahmawati; Ipa Nurlatipah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This research aims to identify the reproduction and development of Bryophyta, especially the moss Octoblepharum albidum. Moss is a group of lower plants that play an important role in ecosystems, especially in humid areas such as tropical rainforests. The method used in this research includes observing the morphology and reproduction of moss using a stereo microscope to observe sporangium and spores. The results showed that Octoblepharum albidum has a lance-shaped leaf morphology, pale green in color, and has a thick texture. There are four brown sporangium, each containing more than 200 spores. This research reveals the importance of Bryophyta in maintaining ecosystem balance and as environmental indicators, as well as providing insight into the factors that influence the growth and development of moss in different habitats.